Comparative Study on Serum Enzyme Levels in Cirrhosis of Liver and Alcoholic Liver Disease (Journal of Basic and Applied Research in Biomedicine, 2022)
Patients with chronic liver diseases are asymptomatic or have only vague non-specific symptoms. Effective medical treatments for chronic liver disease (before cirrhosis is established) are becoming increasingly available and since abnormal LFTs may be the only indication of this diseases. Aims: comparative study on serum Enzyme levels in various liver diseases. Discussion: serum Alkaline phosphatase(ALP), Gamma Glutamyl transferase (Gamma GT), Alanine and Aspartate amino transferases were estimated in viral Hepatitis, Alcoholic liver diseases, Obstructive jaundice, cirrhosis of the liver. It was observed that obstructive jaundice shows higher levels of ALP levels followed by alcoholic liver disease, viral hepatitis, cirrhosis of liver. Viral hepatitis shows higher rise of SGOT, SGPT levels, followed by alcoholic liver disease, obstructive jaundice, and cirrhosis of liver. Gamma Glutamyl transferase enzymes highest levels are seen in alcoholic liver disease. Conclusion: These enzymatic variations are useful to diagnose the disease and classify them according to etiology.